A systematic review of social processes and mechanisms in the community that influence risky sexual behaviour among adolescents and young adults - Youngran Yang; Jieun Jeong; Sung‐Heui Bae (Nursing Open, 2023)
Abstract Aims To examine the associations between social processes and mechanisms within the community and risky sexual behaviour (RSB) among adolescents and young adults. Design Systematic review. Methods We used the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines and conducted a literature search in August 2020. From 11,216 identified articles, 605 were for full‐text screen. We used 24 articles, 22 after applying inclusion criteria and 2 manually searched relevant articles. Results Social processes and mechanisms within the community included collective efficiency and social support, community safety and community norm. Collective efficacy and social support and community safety were examined using 10 and 16 studies, respectively. We found that collective efficiency and social support, and community norms partially supported the occurrences of RSB among adolescents and young adults. Community safety displayed inconclusive relationships with RSB. Conclusions The findings highlight the importance of social processes and mechanisms within the community in preventing RSB among adolescents and young adults. Community‐based programs to improve community efficacy and social support would be effective strategies to reduce such RSB and to promote better reproductive health among adolescents and young adults.